GAMBARAN PENGETAHUAN DAN SIKAP IBU POST PARTUM NORMAL TENTANG TEHNIK MENYUSUI YANG BENAR DI KLINIK SUNGGAL TAHUN 2017 - Rotua Lenawati Tindaon (Jurnal Maternitas Kebidanan, 2018)
The correct breastfeeding technique is a method of breastfeeding the baby with the attachment and position of the mother and baby right. How to breastfeed greatly affects the comfort of baby sucking milk. The midwife or nurse needs to provide counseling to the mother within the first week after childbirth (post partum), about the actual ways of breastfeeding so as not to cause problems. The purpose of this research is to know the description of knowledge and attitude of normal post partum mother about correct breastfeeding technique at Sunggal Medan Clinic Year 2017. This type of research uses descriptive. The population of this study were 16 post partum mothers. Sampling technique by accidental sampling, got sample there are 16 people and use primary and secondary data by distributing questionnaires.The results of this study note that the majority of respondents well knowledge of as many as 8 people (50%), and minority knowledge less as much as 2 people (12.5%) and obtained data that positive majority mothers attitude as many as 10 people (62.5%) and minority respondents have negative attitude that is 6 people (37,5%). Based on this research it is concluded that majority of knowledge of post partum mother about breastfeeding technique is good knowledge, and attitude of mother majority positive attitude. Respondents are expected to seek information and ask many people who have done proper breastfeeding techniques to adapt during the post partum period.